1988
DOI: 10.1246/bcsj.61.4353
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylation of Enynes under Hydroformylation Conditions Catalyzed by Rhodium Carbonyl. A New Method for Synthesis of Cyclic Enones

Abstract: The reactivities of 1-buten-3-yne derivatives toward hydroformylation were studied using a rhodium catalyst. Unexpectedly, cyclopentenone derivatives were obtained in moderate yields together with formylsubstituted dienes and unsaturated lactones. This reaction offers a new method for the catalytic synthesis of cyclopentenones. A mechanism for the cyclic carbonylation of enynes is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Besides the above-mentioned Pd-based protocols, methods involving other catalysts, including Co- [60] and Rh-based complexes [61][62][63][64][65][66]68,69,71,72,[75][76][77] , were reported to undergo hydroformylation of internal alkynes. However, the counterpart methods for terminal alkynes with adequate activity and chemoselectivity remain rather rare.…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides the above-mentioned Pd-based protocols, methods involving other catalysts, including Co- [60] and Rh-based complexes [61][62][63][64][65][66]68,69,71,72,[75][76][77] , were reported to undergo hydroformylation of internal alkynes. However, the counterpart methods for terminal alkynes with adequate activity and chemoselectivity remain rather rare.…”
Section: Proposed Mechanismmentioning
confidence: 99%
“…In contrast to the transition‐metal‐catalyzed hydroformylation of olefins, which is among the most extensively studied catalytic reactions, hydroformylation of alkynes gained rather limited attention over the years [60–78] . This disparity might be surprising, considering that the products, the α,β‐unsaturated aldehydes are important intermediates in organic synthesis, particularly for the synthesis of bioactive compounds, flavors, and fragrances.…”
Section: Pd‐catalyzed Hydroformylation Of Alkynesmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1990, Takahashi and co-workers found that the use of water instead of molecular hydrogen can give cyclocarbonylated products, 2(5H )-furanones, in excellent yield [12][13][14]. Later on, a novel rhodium-catalyzed carbonylation of [15].…”
mentioning
confidence: 99%